2023
DOI: 10.1021/acs.jafc.3c00816
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering the Dissipation of Chlorantraniliprole in Tomatoes: Identifying Transformation Products (TPs) and Coformulants in Greenhouse and Laboratory Studies by UHPLC-Q-Orbitrap-MS and GC-Q-Orbitrap-MS

Abstract: The present study addressed the dissipation of the insecticide chlorantraniliprole in tomatoes treated with Altacor 35 WG under laboratory and greenhouse conditions, as well as the identification of transformation products (TPs) and coformulants, performing suspect screening analysis. Analyses were performed by ultra-high-performance liquid and gas chromatography coupled to quadrupole-Orbitrap high-resolution mass spectrometry (UHPLC-Q-Orbitrap-MS and GC-Q-Orbitrap-MS). In all cases, chlorantraniliprole was fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…A targeted study was carried out to identify the most frequently identified additives in the incurred samples. The 21 additives already detected in previous studies with similar PPP formulations were acquired and searched in tomato samples collected from the greenhouse after the first and second application. , However, only 3 of them were detected in the treated samples, for both treatments, 1,2,4-trimethylbenzene, pentamethylbenzene and biphenyl.1,2,4-trimethylbenzene and biphenyl had been detected in Topas PPP at a concentration of 1.91 and 0.01 g/L, respectively, and 1,2,4-trimethylbenzene and pentamethylbenzene were detected when Altacor PPP was sprayed over tomato cultivation, but they were neither confirmed nor quantified . In this study, they were detected with concentrations for both PPPs treatments between 0.42 and 160.14 μg/kg.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A targeted study was carried out to identify the most frequently identified additives in the incurred samples. The 21 additives already detected in previous studies with similar PPP formulations were acquired and searched in tomato samples collected from the greenhouse after the first and second application. , However, only 3 of them were detected in the treated samples, for both treatments, 1,2,4-trimethylbenzene, pentamethylbenzene and biphenyl.1,2,4-trimethylbenzene and biphenyl had been detected in Topas PPP at a concentration of 1.91 and 0.01 g/L, respectively, and 1,2,4-trimethylbenzene and pentamethylbenzene were detected when Altacor PPP was sprayed over tomato cultivation, but they were neither confirmed nor quantified . In this study, they were detected with concentrations for both PPPs treatments between 0.42 and 160.14 μg/kg.…”
Section: Resultsmentioning
confidence: 99%
“… 10 , 17 19 However, only 3 of them were detected in the treated samples, for both treatments, 1,2,4-trimethylbenzene, pentamethylbenzene and biphenyl.1,2,4-trimethylbenzene and biphenyl had been detected in Topas PPP at a concentration of 1.91 and 0.01 g/L, respectively, 17 and 1,2,4-trimethylbenzene and pentamethylbenzene were detected when Altacor PPP was sprayed over tomato cultivation, but they were neither confirmed nor quantified. 19 In this study, they were detected with concentrations for both PPPs treatments between 0.42 and 160.14 μg/kg. These compounds are derived from benzene, and they could exhibit irritated, toxic, and narcotic effects.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations